Hardy-Leindler-Type Inequalities via Conformable Delta Fractional Calculus - H. M. Rezk; Wedad Albalawi; H. A. Abd El-Hamid; Ahmed I. Saied; Omar Bazighifan; Mohamed S. Mohamed; M. Zakarya (Journal of Function Spaces)
In this article, some fractional Hardy-Leindler-type inequalities will be illustrated by utilizing the chain law, Hölder’s inequality, and integration by parts on fractional time scales. As a result of this, some classical integral inequalities will be obtained. Also, we would have a variety of well-known dynamic inequalities as special cases from our outcomes when α=1.